Increased PD-1+ NK Cell Subset in the Older Population - Deng M; Zeng Y; Liu Y; Wang X; Chen N; Zhang M; Jiang M; Zhao H; Du J (International Journal of General Medicine, 2024)
Meiju Deng,1,2,* Yongqin Zeng,2,3,* Ying Liu,2 Xiaolei Wang,1,2 Na Chen,1,2 Mengyuan Zhang,1,4– 6 Meiqing Jiang,1,4– 6 Hongxin Zhao,2 Juan Du1,4– 6 1Beijing Key Laboratory of Emerging Infectious Diseases, Institute of Infectious Diseases, Beijing Ditan Hospital, Capital Medical University, Beijing, 100015, People’s Republic of China; 2Clinical Center for HIV/AIDS, Beijing Ditan Hospital, Capital Medical University, Beijing, 100015, People’s Republic of China; 3Department of Nephrology, The Affiliated Hospital Guizhou Medical University, Guiyang, Guizhou, 550004, People’s Republic of China; 4Beijing Institute of Infectious Diseases, Beijing, 100015, People’s Republic of China; 5National Center for Infectious Diseases, Beijing Ditan Hospital, Capital Medical University, Beijing, 100015, People’s Republic of China; 6National Key Laboratory of Intelligent Tracking and Forecasting for Infectious Diseases, Beijing, 100015, People’s Republic of China*These authors contributed equally to this workCorrespondence: Juan Du; Hongxin Zhao, Email duj656@ccmu.edu.cn; Drzhao66@ccmu.edu.cnBackground: The aging of the immune system is associated with various diseases. It is worth exploring the changes of the immune system in aging. Previous studies have shown that aged T cells have enhanced expression of co-inhibitory molecules. However, it remains unclear whether aged NK cells exhibit similar characteristics to aged T cells. The objective of our research was to clarify this aspect.Patients and Methods: This study included 98 adults aged 24– 90 years (50 males and 48 females). We detected the subset of peripheral blood NK cells and the expression of various receptors on NK cells among donors of different age groups by flow cytometry. Immune subsets were initially defined by forward and side-scatter characteristics and then staining with the appropriate marker.Results: The absolute number and subset distribution of NK cells were not associated with age. However, CD57 expression and CD69 expression were correlated with age. Furthermore, we found that PD-1 was up-regulated on NK cells in older people, associated with aging, while no such change was observed in other co-inhibitory molecules, including 2B4, CTLA-4, TIM-3, BTLA, CD70, CD39, CD160, and TIGIT. PD-1+ NK cells expressed high levels of CD57 and CD69, indicating PD-1+ NK cells displayed a phenotype of over-activation and aging.Discussion: This study indicated that PD-1+ NK cells were one of the characteristics of NK cells in older people.Conclusion: This study indicated that PD-1+ NK cells were one of the characteristics of NK cells in older people. Those findings provided new ideas to explore the underlying drivers of NK aging.Keywords: PD-1, NK cell, aging, co-inhibitory molecules